Role of stainless steels in desalination (Nickel Institute, 2020)
There are several characteristics of the family of corrosion-resistant steels known as stainless steels that make them highly desirable and eminently qualified for desalination service, not only for piping applications but for all desalting plant systems. This hand book presents applicability of stainless steels for desalination services and desalting plant systems.
"Originally, this handbook was published in 1974 by the Committee of Stainless Steel Producers, American Iron and Steel Institute. The Nickel Institute republished the handbook in 2020."
Keywords: Saline water conversion plants.; Stainless steel.; elektronické knihy; electronic books